Deficiência e interseccionalidade: culturas, políticas e práticas educacionais em debate - Schmidt, Carlo; Menezes, Eliana da Costa Pereira de; Berni, Clenio Perlin; Santos, Mônica Pereira dos; Gomes, Jacqueline de Souza; Moreira, Laura Ceretta (Revista Educação Especial, 2021)
Editorial